Evaluation of liver function tests in the paediatric patient - Víctor Fernández Ventureira; Ignacio Ros Arnal; Gerardo Rodríguez Martínez; Beatriz García Rodríguez; Ruth García Romero; Eduardo Ubalde Sainz (Elsevier, 2021)
Introduction: Although changes in liver function tests can be non-specific in numerous clinical conditions, they can be the first sign of a potentially serious disease in an asymptomatic patient. Material and methods: Retrospective cohort study, performed by reviewing the records of children of a reference hospital central laboratory with alanine aminotransferase enzyme (ALT) elevation during a 6-month aleatory period. Results: 572 blood tests with serum ALT elevation corresponding to 403 patients have been assessed during the period studied. 98 patients were excluded for presenting abnormal liver test before the study period of comorbidity that could produce ALT elevation. The remaining 305 patients, 22.6% were diagnosed with a medical condition during the first blood test that explained the ALT elevation, although only 33.3% of them were followed up until verifying their normalisation. Final study sample consists of 236 patients with abnormal liver test without apparent liver disease. Adequate follow-up was found only in 29% of them. From this group, 9 patients (13%) were diagnosed with liver disease. The rest of the samples were not properly monitored. In patients with higher serum ALT levels, follow-up was early and more appropriate. Conclusions: In our area, most children without apparent liver disease are no properly monitored. Therefore, an opportunity to diagnosis and treat a potential liver disease was lost in a great number of children. All children with unexplained hypertransaminasaemia must be studied. Resumen: Introducción: Las alteraciones del perfil hepático constituyen un hecho inespecífico propio de numerosas condiciones clínicas. Sin embargo, puede implicar la primera manifestación de una patología potencialmente grave en un paciente asintomático. Material y métodos: Estudio observacional retrospectivo que incluye todas las analíticas sanguíneas con elevación de alanino aminotransferasa (ALT) en pacientes pediátricos solicitadas en un sector sanitario en un período de 6 meses. Resultados: Se registraron 572 analíticas correspondientes a 403 pacientes. Se excluyeron 98 pacientes con hipertransaminasemia ya conocida o comorbilidad. De los 305 restantes, el 22,6% se diagnosticaron de patología asociada a hipertransaminasemia, y de estos, se comprobó normalización en el 33,3%. De los 236 pacientes con hipertransaminasemia sin justificar se realizó un seguimiento en el 29%, encontrando patología hepática en 9 pacientes (13% del grupo). En el resto de la muestra no se comprobó analíticamente la evolución de las transaminasas ni la presencia de posible patología hepática. Los pacientes con cifras más elevadas se controlan mejor y antes que los que presentan cifras más bajas. Conclusiones: En nuestra área, la mayoría de los niños sin enfermedad hepática aparente con hallazgo de ALT elevada no son adecuadamente controlados. Esto hace que se pierda una oportunidad única de diagnosticar y tratar precozmente una enfermedad hepática potencial en un gran número de niños. Todo niño con hipertransaminasemia inexplicada debe ser estudiado.